2003
DOI: 10.1002/path.1372
|View full text |Cite
|
Sign up to set email alerts
|

Histological evidence of testicular dysgenesis in contralateral biopsies from 218 patients with testicular germ cell cancer

Abstract: This study was prompted by a hypothesis that testicular germ cell cancer may be aetiologically linked to other male reproductive abnormalities as a part of the so-called 'testicular dysgenesis syndrome' (TDS). To corroborate the hypothesis of a common association of germ cell cancer with testicular dysgenesis, microscopic dysgenetic features were quantified in contralateral testicular biopsies in patients with a testicular germ cell tumour. Two hundred and eighty consecutive contralateral testicular biopsies f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
101
1
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 189 publications
(115 citation statements)
references
References 28 publications
8
101
1
5
Order By: Relevance
“…It is important for the understanding of the pathogenesis of GCNIS-derived TGCT that even though most of the patients are normally virilised males, these neoplasms are associated with disturbed early development of the testis, often manifested in adulthood as clusters of poorly formed tubules, undifferentiated Sertoli cells, microlithiasis and Leydig cells micronodules [9]. Among the risk factors for GCNIS/TGCT, cryptorchidism, genital malformations, low percentage sex chromosome aneuploidy and some forms of infertility, are also linked to disturbed foetal development, hence all these conditions have been grouped within testicular dysgenesis syndrome (TDS) [10].…”
Section: Histopathology and Pathogenesis Of Germ Cell Neoplasmsmentioning
confidence: 99%
“…It is important for the understanding of the pathogenesis of GCNIS-derived TGCT that even though most of the patients are normally virilised males, these neoplasms are associated with disturbed early development of the testis, often manifested in adulthood as clusters of poorly formed tubules, undifferentiated Sertoli cells, microlithiasis and Leydig cells micronodules [9]. Among the risk factors for GCNIS/TGCT, cryptorchidism, genital malformations, low percentage sex chromosome aneuploidy and some forms of infertility, are also linked to disturbed foetal development, hence all these conditions have been grouped within testicular dysgenesis syndrome (TDS) [10].…”
Section: Histopathology and Pathogenesis Of Germ Cell Neoplasmsmentioning
confidence: 99%
“…[37][38][39][40][41][42] 43 have shown a strong correlation between the presence of the Y chromosome and the severity of the gonadal dysgenesis. Gonadoblastoma acts as an 'in situ' precursor in these patients.…”
Section: Pathogenesismentioning
confidence: 99%
“…Gonadoblastoma acts as an 'in situ' precursor in these patients. Recently, Skakkebaek and co-workers 37,42 suggested that many patients with testicular GCT have some evidence of gonadal dysgenesis in the contralateral gonad, be it microlithiasis, Sertoli-cell-only tubules, seminiferous tubules with undifferentiated Sertoli cells or IGCNU. If this is true, it suggests that a specific genetic mutation may not be required to initiate the process of tumor development, but rather environmental factors are sufficient as initiating events.…”
Section: Pathogenesismentioning
confidence: 99%
“…Subsequent research demonstrated a coordinated, dosedependent reduction in expression of key genes and proteins involved in cholesterol transport and steroidogenesis and a corresponding reduction in testosterone in the fetal testes (Lehmann et al, 2004). In humans, similar dysgenetic changes in the histology of the testis have been found in patients with testicular cancer, subfertility, or cryptorchidism (Sohval, 1954(Sohval, , 1956Berthelsen & Skakkebaek, 1983;Hoei-Hansen et al, 2003;Skakkebaek et al, 2003). Furthermore, men with rare genetic abnormalities that cause testicular dysgenesis (e.g.…”
Section: ) Phthalatesmentioning
confidence: 88%